A New Approach for Testing Engagement Characteristics of Clutch. Issue 2 (April 2021) - Zou, Xinyu; Wang, Yang
Abstract: In this paper, a new method for testing the dynamic engagement characteristics of clutch is proposed. This approach is that the dynamic characteristics of clutch is simulated by finite element method. For the fluid friction characteristics, the average Reynolds equation proposed by Patir and Cheng is improved, and dimensionless parameters are adopted, which is applied to calculate the viscous torque. For the boundary friction characteristics, a surface elastic contact model is established to calculate rough contact torque. For the mixed friction characteristics, total torque consists of viscus torque and rough contact torque. The simulation and bench test are completed to verify the validity of model proposed. The model proposed can be used to guide the design of clutch in early stages of product development.